2017
DOI: 10.1039/c7ra10310g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and properties of RbTiOPO4:Ta crystals

Abstract: RTP crystals doped with four different Ta concentrations were grown by high-temperature solution method. Ta dopants changed the growth habit of RTP and the (100) faces were more developed than the other crystal faces. The chemical composition and electronic structure were analyzed using Electron Probe Microanalysis (EPMA) and X-ray photoelectron spectroscopy (XPS). Ta elements could easily incorporate into RTP crystals from the melt due to the large distribution coefficient. As Ta content increased, the Rb 3d,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…As we can see in the table, the binding energy of Ta 4f 7/2 level is 26.4–26.5 eV, which is 0.2–0.3 eV higher than that in RTP:Ta crystal. The spin–orbit doublet separation is 1.9 eV, which is consistent with the data in RTP:Ta crystal . Finally, the relative atomic concentrations for Ta and Ti were estimated from high-resolution XPS data, as shown in Table .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As we can see in the table, the binding energy of Ta 4f 7/2 level is 26.4–26.5 eV, which is 0.2–0.3 eV higher than that in RTP:Ta crystal. The spin–orbit doublet separation is 1.9 eV, which is consistent with the data in RTP:Ta crystal . Finally, the relative atomic concentrations for Ta and Ti were estimated from high-resolution XPS data, as shown in Table .…”
Section: Resultssupporting
confidence: 80%
“…The spin−orbit doublet separation is 1.9 eV, which is consistent with the data in RTP:Ta crystal. 33 Finally, the relative atomic concentrations for Ta and Ti were estimated from high-resolution XPS data, as shown in Table 5. The result shows that relative atomic concentration of Ta actually improves with the increasing doping concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 illustrates the chemical composition of Co-NiO films. It was found that the decrease in an atomic concentration (at%) of Ni 2p is affected by the increase in the content of Co, which is generally found in the report related to dopant 37 . To support the results of the chemical composition in Co-NiO films evaluated by XPS, the EDS was conducted.…”
Section: Resultssupporting
confidence: 61%
“…The explanation could be that the electronegativity difference between Ta and Nb leads to a change of the valence electron density, which influences the ejection of electrons from Nb 5+ ions and thus results in the peak shift. [ 32 ] The high resolution spectra of Ta 4f (Figure 3c) reveal the existence of Ta 5+ in the Ca 2 Nb 3− x Ta x O 10 ( x = 0.5, 1, 1.5) nanosheets, with the Ta 4f 7/2 peak centered on 27.4 eV and Ta 4f 5/2 located at 25.4 eV. And the surface element ratios are shown in Table S2, Supporting Information, which are also coincident with the target ratio.…”
Section: Resultsmentioning
confidence: 99%